Proceedings of the 240 Conference : science's great challenges - Dinner, Aaron R. (Aaron Reuven); Berry, R. Stephen, 1931-; Rice, Stuart Alan, 1932-; Jortner, Joshua (Advances in chemical physics, 2015)
"Based on the '240' Conference held at the University of Chicago in September of 2012, this special volume of The Advances in Chemical Physics series celebrates scientific research contributions and careers of R. Stephen Berry, Stuart A. Rice and Joshua Jortner"--